(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Thiazoles displayed broad range of biological activities and found in many potent biologically active molecules such asSulfathiazol (antimicrobial drug), Ritonavir (antiretroviral drug), Abafungin (antifungal drug) and Tiazofurin(antineoplastic drug). So far, modifications of the thiazole ring have proven highly effective with improved potency andlesser toxicity. The present review highlights the recently synthesized thiazoles possessing important biological activities.